2009
DOI: 10.1080/00268970902997858
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and emission properties of phenylene ethynylene oligomers: effect of substitution and π-conjugation length

Abstract: The optical properties of a series of -conjugated phenylene-ethynylene oligomers (OPEs) have been studied by advanced quantum chemical methods. The ground state and lowest singlet excited state geometries of unsubstituted and different electron donor and acceptor groups substituted OPEs are optimized by density functional theory and configuration interaction singles methods. The absorption and emission spectra of unsubstituted and substituted OPEs have been calculated using the time-dependent density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…Such agreements between observed and computed emission data have been found in a related D-π-A OPE derivative study. [40] The calculated Stokes shifts of 1720-2670 cm -1 are in the same region as the observed Stokes shifts of 1890-2650 cm -1 in cyclohexane (Table 2). Time-resolved emission spectroscopy.…”
Section: Molecular Orbital Computationssupporting
confidence: 63%
“…Such agreements between observed and computed emission data have been found in a related D-π-A OPE derivative study. [40] The calculated Stokes shifts of 1720-2670 cm -1 are in the same region as the observed Stokes shifts of 1890-2650 cm -1 in cyclohexane (Table 2). Time-resolved emission spectroscopy.…”
Section: Molecular Orbital Computationssupporting
confidence: 63%
“…On the basis of these geometries, they calculated the absorption and emission spectra using the TD-DFT method with the B3LYP exchangecorrelation functional, and their results are in good agreement with the experimental results. It has been shown in earlier studies that the results obtained with TD-B3LYP and CIS methods are in good agreement with the available experimental results for phenylene ethynylene oligomers, 45 luciferin, 46 and triphenylene derivatives. 47 Xue et al 48,49 have shown that TD-DFT at PBE1PBE/6-31G//PBE1PBE/6-31G(d) level of theory successfully reproduced the molecular geometry and absorption wavelength of chalcones.…”
Section: Introductionsupporting
confidence: 79%
“…On the other hand, using ab initio CIS/HF, Oumi et al [22] studied chalcone and its hydroxyl derivatives, but the differences reported between gas-phase theoretical and solvated experimental λ max are quite large (0.7eV on average). In recent years, time-dependent density functional theory (TD-DFT) has emerged as a reliable standard tool for the theoretical treatment of electronic excitation spectra and recent works demonstrate the good accuracy for a wide range of systems [23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the computational cost of TD-DFT calculation is comparative to that of a Hartree-Fock based single excitation theory, such as, configuration interaction singles (CIS) or time-dependent Hartree-Fock (TDHF) method.…”
Section: Introductionmentioning
confidence: 99%